(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article describes the purpose of the work was to create local varieties of vegetable mungbeans with an erect stem, non-lodging, with non-cracking pods, large beans, highly productive suitable for mechanized harvesting. They would be well adapted to various soil and climatic conditions and successfully cultivated in all regions of the republic. New varieties would be suitable for sowing after harvesting cereals, vegetables and other crops, be heat-resistant and drought-resistant, and be cultivated on medium-saline soils.